Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

prove: $d\theta = \frac{1}{r^2} \left( x\;dy - y\;dx \right)\quad\text{where }r^2 = x^2 + y^2$. Full solution would be appreciated. please show your step because i can't follow if you skip the step

share|cite|improve this question
@mixedmath - i didn't study calculus yet but i try to self study myself, so i really mess up to figure myself. – Victor Oct 15 '11 at 0:20
up vote 3 down vote accepted

let $x=r\cos\theta$ and $y=r\sin\theta$. then differentiate both with respect to $\theta$ then multiply $\frac{\text{d}x}{\text{d}\theta}$ by $y$ and then $\frac{\text{d}y}{\text{d}\theta}$ by $x$. find their difference and send $\text{d}\theta$ to the other side to obtain the result. This should be very easy to follow because $$x\left(\frac{\text{d}y}{\text{d}\theta}\right)-y\left(\frac{\text{d}x}{\text{d}\theta}\right)=x^2+y^2=r^2.$$ Remember that, $\frac{\text{d}x}{\text{d}\theta}=-r\sin\theta=-y$. So, $y\frac{\text{d}x}{\text{d}\theta}=-y^2$. Similarly, $\frac{\text{d}y}{\text{d}\theta}=r\cos\theta=x$. So, $x\frac{\text{d}y}{\text{d}\theta}=x^2$. Then, $$x\frac{\text{d}y}{\text{d}\theta}-y\frac{\text{d}x}{\text{d}\theta}=x^2+y^2=r^2.$$ Thus, $(x\text{d}y-y\text{d}x)/\text{d}\theta=r^2$ and the result follows.

share|cite|improve this answer
i can't follow, please help – Victor Oct 15 '11 at 0:51
Victor, You should be fine now. I have provided the full solution to the problem. – smanoos Oct 15 '11 at 1:07

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.